2004
DOI: 10.1089/109065704323016012
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Variations in Knowledge and Attitudes about Genetic Testing

Abstract: This study was designed to shed light on whether differences in utilization of genetic testing by African-Americans, Latinos, and non-Hispanic Whites are due primarily to different preferences, or whether they instead reflect other values and beliefs or differential access. It explores the values, attitudes, and beliefs of African-Americans, Latinos, and non-Hispanic Whites with respect to genetic testing by means of a telephone survey of representative samples of these three groups. The study finds clear evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
153
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 20 publications
10
153
1
Order By: Relevance
“…In a national telephone survey that included 375 African Americans and 960 whites, African Americans were more likely than whites to indicate that they would want genetic testing for both "untreatable diseases" in general and Huntington disease specifically. 82 Similarly, a survey of 174 African Americans and 278 whites specifically focusing on attitudes toward predictive testing for AD found that African Americans expected fewer negative consequences from a positive genetic test result for AD than whites. 78 The REVEAL study will add to this literature with respect to predictive genetic testing for common, complex conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a national telephone survey that included 375 African Americans and 960 whites, African Americans were more likely than whites to indicate that they would want genetic testing for both "untreatable diseases" in general and Huntington disease specifically. 82 Similarly, a survey of 174 African Americans and 278 whites specifically focusing on attitudes toward predictive testing for AD found that African Americans expected fewer negative consequences from a positive genetic test result for AD than whites. 78 The REVEAL study will add to this literature with respect to predictive genetic testing for common, complex conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our results may not be representative of the population of survivors and parents, and requires verification in a larger sample representing different cultural and religious groups. 31,32 As base knowledge of testing appeared low in this sample, participants may not have fully understood the implications of genetic testing for risk of late effects. Different types of genetic tests for different late effects (e.g.…”
Section: Limitationsmentioning
confidence: 89%
“…A number of recent studies have begun to explore the potential impact of genetic knowledge on views regarding genetics and geneenvironment interactions (Christensen et al 2010;Jayaratne et al 2009;Singer et al 2004). One study for example found that African-American and Latino participants were less likely to utilize genetic services based on a lack of knowledge provided to them through their health care providers (Suther and Kiros 2009).…”
Section: Discussionmentioning
confidence: 99%